2016
DOI: 10.1021/acs.joc.6b01685
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of High Stereoselectivity in Di-tert-butylsilylene-Directed α-Galactosylation

Abstract: The origin of the high α(1,2-cis)-stereoselectivity in the reaction of galactosyl and galactosaminyl donors with a di-tert-butylsilylene (DTBS) group with several nucleophiles has been elucidated by means of experimental and computational approaches. DTBS overcomes any other cyclic protecting groups examined to date and the β(1,2-trans)-directing effect due to the neighboring participation by CO groups at C2. Requirements for the α(1,2-cis)-stereoselectivity are as follows: (1) generation of an oxocarbenium io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 71 publications
0
41
0
Order By: Relevance
“…Thus,t reatment of glycal 18 with 3c under photoirradiation gave an oxazolidine intermediate, [30,31a] which underwent Lewis-acidcatalyzed glycosylation with as eries of alcohols 19 a-c to afford the corresponding aminosugar conjugates 20 a-c in 54-58 %y ields. [32] This type of 1,2-aminoalcoxylation is sometimes difficult using N-sulfonyliminoiodinanes because of the relative instability of the aziridine intermediate, [30,31b,33] whereas conjugation with aminosugars offers apowerful tool for drug discovery. [11,34] In conclusion, we have demonstrated that the coordination of an ortho-methoxymethyl group effectively stabilizes N-acyliminoiodinanes,e nabling the first synthesis and characterization of their structure.T he X-ray structure revealed that the carbonyl oxygen atom coordinates to the iodine atom of the iminoiodinane.A dditionally,t he N-acyliminoiodinane could be activated to react with silyl enol ethers under photoirradiation conditions.T his method was successfully expanded to various N-sulfonyliminoiodinanes.W eb elieve that the present activation method of iodinanes will encourage greener approaches for the introduction of amino groups, and further develop the understanding of hypervalent iodine chemistry.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thus,t reatment of glycal 18 with 3c under photoirradiation gave an oxazolidine intermediate, [30,31a] which underwent Lewis-acidcatalyzed glycosylation with as eries of alcohols 19 a-c to afford the corresponding aminosugar conjugates 20 a-c in 54-58 %y ields. [32] This type of 1,2-aminoalcoxylation is sometimes difficult using N-sulfonyliminoiodinanes because of the relative instability of the aziridine intermediate, [30,31b,33] whereas conjugation with aminosugars offers apowerful tool for drug discovery. [11,34] In conclusion, we have demonstrated that the coordination of an ortho-methoxymethyl group effectively stabilizes N-acyliminoiodinanes,e nabling the first synthesis and characterization of their structure.T he X-ray structure revealed that the carbonyl oxygen atom coordinates to the iodine atom of the iminoiodinane.A dditionally,t he N-acyliminoiodinane could be activated to react with silyl enol ethers under photoirradiation conditions.T his method was successfully expanded to various N-sulfonyliminoiodinanes.W eb elieve that the present activation method of iodinanes will encourage greener approaches for the introduction of amino groups, and further develop the understanding of hypervalent iodine chemistry.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The trisaccharide acceptor was synthesized as depicted in Scheme 1. The Galα(1,4)Gal disaccharide 6 was obtained by di-tert-butylsilylene (DTBS)-directed α-galactosylation [29,30]. In this reaction, the formation of an undesirable orthoester was inevitable due to 2-O-Bz of 4.…”
Section: Synthesis Of the Trisaccharide Common Acceptormentioning
confidence: 99%
“…This compound was further glycosylated with 7 under NIS/AgOTf-promoted conditions at À30 8C to generatep entasaccharide 20 in 69 %y ield. Treatment of 20 with 1% TFAi nd ichloromethane resultedi nt he removalo f the PMB group in 88 %y ield generating 21.G lycosylation of 21 with 8 [12] gave the desired hexasaccharide 22 with exclusive a-selectivity [13] in 89 %y ield. The successo ft his "counter-clockwise" approacht oi ntroducing the substituents onto the fucose residue can be rationalized by the need to glycosylate the least reactive (axial) alcohol first, followed by OH-3 andf inally OH-2.…”
mentioning
confidence: 99%